Mapped infinite patches for the NURBS based boundary element analysis in geomechanics. (May 2015) - Beer, G.
Abstract: A formulation of infinite NURBS patches is presented which allows the modeling of infinite surfaces with the NURBS based boundary element method. Applications are the modeling of long tunnels and of the ground surface in geotechnical work. To achieve an infinite surface, special mapping functions are used for describing the geometry. For the description of the displacements either a constant variation is assumed simulating plane strain conditions or it is assumed that the displacements decay to zero at infinity. The theory and implementation details are presented. Test examples show that the proposed formulation works well for the simulation of long tunnels and of the ground surface. Finally a practical example of a tunnel intersection is presented.